CURRENT UNDERSTANDING OF THE ETIOLOGY OF CHRONIC GENERALIZED PERIODONTITIS - Alimova, D.M.; Fazilova, L.; Mukimov , O.A.; Eshimova , P.E.; Ismailova, S.S. (Educational Research in Universal Sciences, 2023)
This literature review presents the etiological factors that lead to one of the most common periodontal diseases - chronic generalized periodontitis. The main role belongs to the bacterial biofilm, it is the cause of the disease development. In addition, immune disorders can also be a cause of periodontal disease.